Pancreas and Coronavirus Disease-2019 - Lorenzo Dioscoridi (Pancreas, 2025)
Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) virus affects many other organs than lung and upper airways. Gastrointestinal system appears to be affected both in the upper and in the lower portions. Moreover, hepatic, myocardial, and renal involvements are reported. Furthermore, pancreas can be affected in coronavirus disease-2019 (COVID-19) and the presence of SARS-COV-2 in the pancreatic tissue has been confirmed during autopsy.1This is related to the presence of angiotensin-converting enzyme type 2 (ACE-2) receptor localized both in the exocrine and endocrine parts of pancreas. Thus, Yang et al2 and colleagues reported frequent hyperglycemia in SARS-COV infections that can be related to damage of pancreatic islets (through ACE-2 binding).